New Onset Post-Operative Seizures Associated with Ventriculoperitoneal Shunts; A Retrospective Study (Medical Forum Monthly, 2024)
Objective: To establish the frequency of post-operative seizures in patients treated with ventriculoperitoneal shunt, either first or revised, so that the role of post procedural prophylactic anti-epileptic drug administration could be established.Study Design: Retrospective observational studyPlace and Duration of Study: This study was conducted at the Liaquat National Hospital, Karachi from January 2010 to December 2017.Materials and Methods: The sampling technique used was retrospective non-probability sampling. The sample size for this study was 76 and was calculated using WHO sample size calculator.The Inclusion criteria were established that included patients operated with VP shunt within the duration mentioned above. Patients above the age of 60 years, having history of seizures previous to the procedure, and history of previous cerebral trauma were excluded from the study.Results: The mean age of the patients was found to be 26.7±18.74. The results of this study reveal that out of the 76 patients included in the study 2 (2.63%) patients developed new onset seizures associated with ventriculoperitoneal shunt. None of the patients received Levitracetam or any other antiepileptic drug prophylactically in the post-operative period.Conclusion: It is concluded from this study that new onset seizures are a relatively non significant risk in the post operative management and care of patient and anti epileptics do not have a significant role in preventing such episode.